Reducing the Linnean and Wallacean shortfalls to Anacroneuria Klapálek, 1909 (Plecoptera: Perlidae) from Brazil: two new species and several new distributional records - de Almeida, Lucas Henrique [UNESP]; de Carvalho Gonçalves, Maísa; da Conceição Bispo, Pitágoras [UNESP] (Springer Nature, 2025)
Anacroneuria is the most diverse genus in the Perlidae family, with about 100 species recorded in Brazil. The genus is distributed throughout the country and has high diversity. However, this diversity is probably underestimated, which implies the need to carry out more studies on the group in order to help reducing the Linnean and Wallacean shortfalls. In this paper, we studied Brazilian Anacroneuria deposited in the Aquatic Insect Collection Prof. Dr. Cláudio Gilberto Froehlich (CIACGF at São Paulo State University – UNESP, Assis, SP, Brazil), the Entomology Museum of the Federal University of Viçosa (UFVB, Viçosa, MG, Brazil), and the Museum of Zoology of the University of São Paulo (MZUSP, São Paulo, SP, Brazil). As a result, we studied 20 already known species (Anacroneuria bahiensis, A. boraceiensis, A. cathia, A. fittkaui, A. flintorum, A. itajaimirim, A. marlieri, A. mineira, A. minuta, A. ofaye, A. otafroehlichi, A. pakitza, A. paprockii, A. plaumanni, A. polita, A. singela, A. singularis, A. stanjewetti, A. tabatae, A. vanini) and describe two new species: A. duarte sp. n. and A. sallesi sp. n. In adittion, we present occurrence maps highlighting the new records for all species and discuss important morphological variations of some of them. The new species described and the new geographic records presented contribute to reducing the Linnean and Wallacean deficits for Brazilian Anacroneuria (Plecoptera: Perlidae).
Keywords: Aquatic insects; Biodiversity; Distribution; Freshwater; Stoneflies